A novel occluder for endoscopic closure of gastrotomy: an ex vivo and in vivo animal study - Kim, Ji Hee; Lee, Bo-In; Lee, Sung Hak; Kim, Joon Sung; Baeg, Myong Ki; Park, Jae Myung; Lee, In-Seok; Kim, Byung-Wook; Kim, Sang Woo; Choi, Hwang; Choi, Myung-Gyu (Endoscopy, 2016)
Background and aims: We evaluated the feasibility of a novel occluder for endoscopic closure of natural orifice transluminal endoscopic surgery (NOTES) gastrotomy.Methods: The occluder is a self-expandable, membrane-covered, metal structure for endoscopic delivery through gastrointestinal (GI) wall defects. The procedure time and air-tightness of endoscopic closure for a 12-mm perforation were compared for a through-the-scope clip group and an occluder group in an ex vivo animal study. The feasibility and safety of the occluder for the closure of NOTES gastrotomy were also evaluated in an in vivo animal study. Results: In the ex vivo study, the median procedure time for closure was significantly shorter and the minimum air-leakage pressure was significantly greater in the occluder group than in the endoclip group. In the in vivo study, immediate air-tight sealing was achieved by application of the occluder and there were no serious adverse events. All animals showed spontaneous detachment of the occluder into the gastric lumen and complete healing within 4 – 8 weeks.Conclusions: The novel occluder can provide immediate and permanent sealing for NOTES gastrotomy.